Face yourself: The social neuroscience of mirror gazing - Tramacere, Antonella (Frontiers in Psychology, 2022)
In philosophical and psychological accounts alike, it has been claimed that mirror gazing is like looking at ourselves as others. Social neuroscience and social psychology offer support for this view by showing that we use similar brain and cognitive mechanisms during perception of both others’ and our own face. I analyse these premises to investigate the factors affecting the perception of one’s own mirror image. I analyse mechanisms and processes involved in face perception, mimicry, and emotion recognition, and defend the following argument: because perception of others’ face is affected by our feelings toward them, it is likely that feelings toward ourselves affect our responses to the mirror image. One implication is that negative self-feelings can affect mirror gazing instantiating a vicious cycle where the negative emotional response reflects a previously acquired attitude toward oneself. I conclude by discussing implications of this view for psychology and social studies.